Uma contribuição para mensuração dos ativos biológicos e produto agrícola sem mercado ativo e seus reflexos contábeis - Ribeiro, Douglas Tadeu de Oliveira (2013)
The present study contributed to establish a cash flow model to measure the fair value of any biological asset teaching through examples based on best practices in asset valuation used by the market. Although CPC 29 (equivalent to international financial reporting standard IAS 41) establishes a level of hierarchy for measuring fair value, many assessments are performed using the discounted cash flow, in the absence of an active market or in the absence of market for the asset in its present condition, even if there is an active market for the mature biological asset. Given this difficulty, the method of discounted cash flow for the present value is used to evaluate a wider range of biological assets. The main aspect discussed was how to translate the elements necessary for an asset valuation by the method of discounted cash flow applied to different crops and also livestock. The accounting effects are different for each type of entity, farming or agribusiness, as well as its effects on the distribution of dividends and tax treatment. This study also evaluate the need for modification of internal controls to account for the fair value of agricultural produce for industrial entities and its practical implications. Since it is a relevant estimate in the financial statements, the measurement must be accompanied by extensive disclosures of significant assumptions used, which has not yet happened in the disclosures analyzed listed Brazilian companies. In many cases the disclosure makes comparison between companies operating in the same sector, since important information is not disclosed. The study also considers the effects of fair value of biological assets on the financial statements of the public entities and if the notes are sufficient to provide user with enough information to allow comparison